2007
DOI: 10.1016/j.physletb.2007.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic-ray positron fraction measurement from 1 to 30 GeV with AMS-01

Abstract: A measurement of the cosmic ray positron fraction e+/(e++e−)e+/(e++e−) in the energy range of 1–30 GeV is presented. The measurement is based on data taken by the AMS-01 experiment during its 10 day Space Shuttle flight in June 1998. A proton background suppression on the order of 106 is reached by identifying converted bremsstrahlung photons emitted from positrons

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
193
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(254 citation statements)
references
References 15 publications
61
193
0
Order By: Relevance
“…Especially the PAMELA data confirm the hint of excess of positron fraction previously discovered by HEAT [7,8] and AMS [9]. Many theoretical models have been proposed to explain these phenomena in past years, among which a class of leptonic dark matter (DM) annihilation models is of particular interest (e.g., [10,11] or see the review [12]).…”
Section: Introductionsupporting
confidence: 60%
“…Especially the PAMELA data confirm the hint of excess of positron fraction previously discovered by HEAT [7,8] and AMS [9]. Many theoretical models have been proposed to explain these phenomena in past years, among which a class of leptonic dark matter (DM) annihilation models is of particular interest (e.g., [10,11] or see the review [12]).…”
Section: Introductionsupporting
confidence: 60%
“…Since τ E determines the positron propagation scale, the related Table 1. Data are taken from CAPRICE (Boezio et al 2000), HEAT (Barwick et al 1997), AMS (Aguilar et al 2007;Alcaraz et al 2000) and MASS (Grimani et al 2002). uncertainties should have a far stronger effect on the primary contributions with a far greater spatial (or time) dependency, such as for instance nearby astrophysical or exotic point sources.…”
Section: Energy Lossesmentioning
confidence: 99%
“…Positrons are drifted away from the Galaxy and their flux at the Earth is depleted. We note that diffusive reacceleration and Galactic convection were included separately by Lionetto et al (2005) in (Boezio et al 2000), HEAT (Barwick et al 1997), AMS (Aguilar et al 2007;Alcaraz et al 2000) and MASS (Grimani et al 2002). their prediction of the positron spectrum, with the net result of either overshooting (diffusive reacceleration) or undershooting (galactic convection) the data. If we now incorporate both processes and add the various energy-loss mechanisms, we derive the dotted curve, which also contains a bump, although of far smaller amplitude.…”
Section: Diffusive Reacceleration and Full Energy Lossesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent measurements of cosmic ray electrons and positrons have been interpreted as possible evidence for dark matter [1][2][3][4][5][6]. In particular, it has been suggested that the features of the e þ e À spectrum and positron fraction reported by PAMELA [1], ATIC [2], PPB-BETS [3], the Fermi Gamma Ray Space Telescope (FGST) [4], HEAT [5], and AMS-01 [6] may originate from either DM annihilations [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] or decays [22][23][24][25][26][27] taking place in the Galactic Halo.…”
Section: Introductionmentioning
confidence: 99%